Housing production as a consumer good - Leal del Castillo, Gabriel Enrique (Universidad Antonio Nariño, 2021)
The article deals with the issue of housing development in urban areas, emphasizing on the environmental impacts that such industry produces at different levels, taking into account the processes that disturb and deteriorate natural surroundings, before, during and after the construction of those residences. Starting from Bertalanffy’s General System Theory, the author analyzes the various systems taking part in the so-called Urban Ecosystem: the natural system, the administrative system, the urban system, the transportation system, the economical system and the social system. Afterwards, it presents the impacts of the construction industry and the urban growth in Bogota, while the installment of green councils for sustainable construction both in the world and in Colombia goes on simultaneously. Hence, the author concludes that entering into a clean production and green market phaseis a priority for the construction industry in the country.